Improved Viscoelastic Damping Properties of Carbon Black Reinforced EPDM Composites by Blending with ENR - Kejian, Wang; Zhicheng, Jia; Zhongfeng, Zhang; Gaolin, Pei; Honggang, Jiang; Zhengtao, Su (Journal of Composites and Biodegradable Polymers, 2020)
EPDM/ENR blends were prepared from saturated nonpolar ethylene propylene diene monomer (EPDM) and unsaturated epoxidized natural rubber (ENR). The dynamic mechanical properties of EPDM/ENR compounds and their vulcanizates were studied by rubber processing analyzer and dynamic mechanical thermal analyzer. The results show that the addition of ENR is helpful to improve EPDM processability. With the increase of ENR content, the tensile strength of EPDM/ENR decreases first and then increases while the elongation at break increases. The lowest tensile strength is still greater than 12.5MPa, which shows the industrial usage. The temperature range for the loss factor being greater than 0.1 becomes wider from -40.1 ˚C 7.7 ˚C for pure EPDM to -40.1 ˚C 80 ˚C for 80 : 20 EPDM/ENR.